Horizontal antimicrobial resistance transfer drives epidemics of multiple Shigella species - Kate S. Baker (Nature Portfolio, 2018)
Antimicrobial resistance (AMR) in Shigella species is a public health concern. Here, Baker et al. show how horizontal transfer of an AMR plasmid among Shigella species contributes to epidemics in men who have sex with men in England.